PLA's new military revolution : developing talent - Li, Mingjiang (2009)
The PLA underwnet a dazzling round of reshuffles of senior officers in the past few months, including the job transfer of former deputy chief of General Staff Zhang Qinsheng. This new round of military personnel changes has to be understood in the broader context of China's new military revolution programme. The PLA is taking concrete measures, including reforms in the personnel system, to train military commanders with comprehensive skills in order to cope with demands and rquirements of its "leap-frong" military revolution - and to retain its talent.